«Health school» for arterial hypertension patients: district out-patient clinic experience - A. N. Andreev; N. V. Izmozherova; G. B. Kolotova; S. N. Makhlina; A. A. Popov; A. V. Akimova; O. Yu. Stryukova; N. V. Tagiltseva; M. I. Fominykh (Кардиоваскулярная терапия и профилактика)
Aim. To analyze effectiveness of “Health School” (First Out-Patient Department, Yekaterinburg Central City Hospital No. 6) activity in arterial hypertension (AH) patients. Material and methods. The study included 120 patients (85 females), attending School sessions. Attendees’ questionnaire survey was performed at first and sixth sessions. Target blood pressure (BP) level achievement was assessed by office BP measurement and diary BP registration. Six-month results after stopping the program were also registered. Results. Among all participants, there were 70.8% females; 67 individuals under 60 were still working (58.3%), 41 had Stage I AH (34%). By the program’s end, 30 patients (25%) achieved target BP levels; in 42 individuals (35%), BP decreased by 30% from the baseline level. Six months later, 67 patients (55.8%) maintained target BP level. Increase in combination therapy usage, by the end of the program, was associated with increased administration of diuretics and angiotensin II receptor antagonists. Conclusion. Optimal program outlay included interactive lectures and individual consultation sessions, that gave a chance to reach wide audience of AH patients and achieve real-life positive results in their treatment.